Mucocutaneous Lymph Node Syndrome temporally related to COVID-19 (Kawasaki-like Syndrome) in Pediatric Patients - Calderón-Baldera, Karen Eliana (2020)
Introduction: The Inflammatory Multisystemic Syndrome arises as a manifestation of COVID-19 in the pediatric age, with diverse phenotypes within which a Kawasaki-like Syndrome is found, which responds to the usual therapy for classic disease. Case reports: Two cases from Chiclayo city, 7 and 9 years old, female sex, history of probable and confirmed contacts for COVID-19, and one of the patients with positive IgG serology and compatible tomographic images with COVID-19 in resolution. Both met criteria for Pediatric Inflammatory Multisystemic Syndrome and classic Kawasaki Disease, in addition with a favorable response to usual therapy, without complications and in current follow-up. Conclusions: the reported cases respond to usual therapy and the presentation characteristics will contribute to the documentation of this emerging pathology in the scientific community.